PHYTOTOXICITY AND ENZYMATIC ACTIVITY IN SOILS OF KALMYKIA UNDER THE INFLUENCE OF OIL POLLUTION - Aleksey A. Buluktaev (Юг России: экология, развитие, 2017)
Abstract. The aim is to study the change in the enzymatic activity in Kalmykia soils under oil pollution, as well as to study the phytotoxicity of contaminated soils. Methods. A laboratory experiment was conducted to study the phytotoxicity and enzymatic activity in soils. As objects of research, brown semidesert, light chestnut and chernozem soils (Black soil) were selected. Common bean was chosen as the testing culture. The levels of oil pollution in the study area were different. The phytotoxicity of soils was identified by the germination, the length of the terrestrial part of the plants, the length of the root and the total biomass. The enzymatic activity in soils was determined by the methods of T.A. Shcherbakova, Shtefanika, Yarni, Tomesku, A.Sh. Galstyan, F.KH. Khazieva, Ya.M. Agaforova, A.E. Gulko. Results. As a result of the conducted studies it was revealed that the soils of Kalmykia are not resistant to oil pollution, even insignificant concentrations of oil cause a change in the enzymatic activity in soils. All investigated oil contaminated soil samples show a negative impact on the growth of testing-culture plants, germination decreases, the length of the ground and underground parts of plants is reduced. Conclusions. It has been proved that oil pollution affects the change in the enzymatic activity in Kalmykia soils, and, the greater the concentration of oil contamination, the stronger this change can be traced. Oil-contaminated soils show a strong phytotoxic effect in relation to the plants under study.